Measurement of the water-Cherenkov detector response to inclined muons using an RPC hodoscope - Assis, Pedro (2015)
The Pierre Auger Observatory operates a hybrid detector composed of a Fluorescence Detector and a Surface Detector array. Water-Cherenkov detectors (WCD) are the building blocks of the array and as such play a key role in the detection of secondary particles at the ground. A good knowledge of the detector response is of paramount importance to lower systematic uncertain- ties and thus to increase the capability of the experiment in determining the muon content of the extensive air showers with a higher precision. In this work we report on a detailed study of the detector response to single muons as a function of their trajectories in the WCD. A dedicated Resistive Plate Chambers (RPC) hodoscope was built and installed around one of the detectors. The hodoscope is formed by two stand-alone low gas flux segmented RPC detectors with the test water-Cherenkov detector placed in between. The segmentation of the RPC detectors is of the order of 10 cm. The hodoscope is used to trigger and select single muon events in different ge- ometries. The signal recorded in the water-Cherenkov detector and performance estimators were studied as a function of the trajectories of the muons and compared with a dedicated simulation. An agreement at the percent level was found, showing that the simulation correctly describes the tank response.